α-Synuclein ubiquitination – functions in proteostasis and development of Lewy bodies - Hung-Hsiang Ho; Hung-Hsiang Ho; Simon S. Wing; Simon S. Wing (Frontiers in Molecular Neuroscience)
Synucleinopathies are neurodegenerative disorders characterized by the accumulation of α-synuclein containing Lewy bodies. Ubiquitination, a key post-translational modification, has been recognized as a pivotal regulator of α-synuclein’s cellular dynamics, influencing its degradation, aggregation, and associated neurotoxicity. This review examines comprehensively the current understanding of α-synuclein ubiquitination and its role in the pathogenesis of synucleinopathies, particularly in the context of Parkinson’s disease. We explore the molecular mechanisms responsible for α-synuclein ubiquitination, with a focus on the roles of E3 ligases and deubiquitinases implicated in the degradation process which occurs primarily through the endosomal lysosomal pathway. The review further discusses how the dysregulation of these mechanisms contributes to α-synuclein aggregation and LB formation and offers suggestions for future investigations into the role of α-synuclein ubiquitination. Understanding these processes may shed light on potential therapeutic avenues that can modulate α-synuclein ubiquitination to alleviate its pathological impact in synucleinopathies.